Улогата, значењето и поврзаноста на корпоративно-општествената одговорност и односите со јавноста во експанзијата на маркетинг комуникацискиот микс - Наумовска, Љупка (Економски факултет, УКИМ, Скопје, 2014)
The companies, organizations and institutions are using communication tools In order to communicate with their current and potential customers. Global and local market conditions are constantly changing and customers are become more sensitive, more resistant to traditional advertising messages and hence, becoming over advertised. All these factors are creating requirement for altering the structure of the traditional marketing communication mix elements. Additional factor for changing the marketing communication mix are the financial and social consequences from the world economic crisis that relocated the standards in the globe. One method for improvement of marketing communication‟s mix efficiency is by reallocation the leading role of advertising with public relations. The practice of public relations tools ensure higher level of transparency in internal and external organizational communications and thus creates better performing. As a parallel trend, the number of companies involved in corporate - social activities is increasing. Corporate social responsibility is still a discipline without structural definition and belonging. Companies that are practicing corporate social responsibility have better image, reputation and sales results. Hence, the inclination for integrating corporate social responsibility and marketing communication mix and upgrading its functionality. The new, upgraded marketing communication mix will correspond with the thee buying habits and characteristics of the customers, new market conditions and media.
The role, meaning and relation between Corporate Social Responsibility and Public Relations in marketing mix expansion
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Нада Секуловска.
Keywords: communication, corporate social responsibility marketing, public relations, advertising, reputation, image, cause